Archaeal and bacterial communities in deep-sea hydrogenetic ferromanganese crusts on old seamounts of the northwestern Pacific. - Shota Nitahara; Shingo Kato; Akira Usui; Tetsuro Urabe; Katsuhiko Suzuki; Akihiko Yamagishi (PLoS ONE, 2017)
Deep-sea ferromanganese crusts are found ubiquitously on the surface of seamounts of the world's oceans. Considering the wide distribution of the crusts, archaeal and bacterial communities on these crusts potentially play a significant role in biogeochemical cycling between oceans and seamounts; however little is known about phylogenetic diversity, abundance and function of the crust communities. To this end, we collected the crusts from the northwest Pacific basin and the Philippine Sea. We performed comprehensive analysis of the archaeal and bacterial communities of the collected crust samples by culture-independent molecular techniques. The distance between the sampling points was up to approximately 2,000 km. Surrounding sediments and bottom seawater were also collected as references near the sampling points of the crusts, and analyzed together. 16S rRNA gene analyses showed that the community structure of the crusts was significantly different from that of the seawater. Several members related to ammonia-oxidizers of Thaumarchaeota and Betaproteobacteria were detected in the crusts at most of all regions and depths by analyses of 16S rRNA and amoA genes, suggesting that the ammonia-oxidizing members are commonly present in the crusts. Although members related to the ammonia-oxidizers were also detected in the seawater, they differed from those in the crusts phylogenetically. In addition, members of uncultured groups of Alpha-, Delta- and Gammaproteobacteria were commonly detected in the crusts but not in the seawater. Comparison with previous studies of ferromanganese crusts and nodules suggests that the common members determined in the present study are widely distributed in the crusts and nodules on the vast seafloor. They may be key microbes for sustaining microbial ecosystems there.